An exploration of determinants of affordable housing choice. Issue 5 (28th September 2017) - Olanrewaju, AbdulLateef; Woon, Tan Chai
Abstract : Purpose: Housing sufficiency is an indication of national development, and in recognition of this, a longstanding development objective of the Malaysian Government is the provision of affordable housing. The government has introduced various policies, schemes and regulations to increase housing supply. However, despite these measures, homeownership rates are dropping, and housing prices are outstripping inflation. For this reason, this paper aims to explain the determinants of housing choices. The issues in affordable housing supply in Malaysia are that of shortage and distributions. The problem of distribution is largely addressable through choice reconciliations. Design/methodology/approach: The research is based on a cross-sectional survey questionnaire, comprising 20 determinants and 468 householders/users. The questionnaire was developed via a review of the literature and the authors' experience. The survey forms are administered by hand. Findings: Six determinants were found to be extremely important to households' choice of housing. The Kaiser's measure of sampling adequacy (MSA) indicated that the strength of the relationships among the determinants was strong (MSA = 0.762). Bartlett's test of sphericity, was significant χ 2 (1035) = 5013.814, p < 0.001), indicating the data were drawn from the same population and that the determinants were related. Using principal component analysis, all the 20 determinants were reduced to seven factors that accounted for some 60 per cent of the total proportion communalities. The factors were general factor, financial factor, building factor, income factor, accessibility factor, market factor and location factor. Originality/value: Previous research only addressed factors affecting housing price, not a choice. This is the first study that explains determinants of housing choice determinants in Malaysia. This is the first study that involves large respondents. Previous research addressed housing in general and not affordable housing. The results will be useful to developers, homebuyers and policy makers towards affordable housing delivery.